Give your greens a home for life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Greenhouses and shelter structures for tropical regions FAO Plant Production and Protection Papers no. 154. 1999. 138 pp. ISBN 9251043868 US$34 E 39.50 FAO Sales and Marketing Group Viale delle Terme di Caracalla, 00100 Rome, Italy. Fax: +39 06 57 0